Social norms and preferences for generosity are domain dependent - Hande Erkut (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
Experimental research on generosity has focused predominantly on behavior in the monetary domain, although many real life decisions take place in the non-monetary domain. Investigating generosity preferences in the non-monetary domain is important to understand a large class of situations ranging from effort provision at work to individual CO2 emissions. This study explores whether generosity differs between the monetary and non-monetary domains and if so why. The results show that preferences for generosity are different between domains and that different social norms of allocation can explain the greater levels of generosity in the non-monetary compared to the monetary domain.
Keywords: D03; D64; C91; 330; generosity; dictator game; non-monetary domain; GARP; social norms